Between dog and wolf: the sophist as teacher - Torrano, Jaa (2015)
In the prologue of Plato's Sophist, two views about the sophist are presented: 1) the benevolent one of Socrates, who is willing to consider the possibility that the sophist, the statesman, and the philosopher all belong to the same kind; 2) the hostile and critical one of the Stranger from Elea. In the course of the dialogue, it can be seen that Socrates' initial view proves to be the more correct and to prevail over that of the Stranger from Elea.